A comparison of rib cortical bone compressive and tensile material properties: Trends with age, sex, and loading rate - Albert, Devon L.; Katzenberger, Michael J.; Agnew, Amanda M.; Kemper, Andrew R. (Journal of the mechanical behavior of biomedical materials, 2021)
The objectives of this study were to develop novel methods for quantifying human rib cortical bone material properties in compression and to compare the compressive material property data to existing tensile data for matched subjects. Cylindrical coupons were obtained from the rib cortical bone of 30 subjects (M = 19, F = 11) ranging from 18 to 95 years of age (Avg. = 48.5 ± 24.3). Two coupons were obtained from each subject. One coupon was tested in compression at 0.005 strain/s, while the other coupon was tested in compression at 0.5 strain/s. Load and displacement data were recorded so that the elastic modulus, yield stress, yield strain, ultimate stress, ultimate strain, elastic strain energy density (SED), plastic SED, and total SED could be calculated. All compressive material properties were significantly different between the two loading rates. An ANOVA revealed that sex alone had no significant effect on the compressive material properties. The interaction between sex and age was significant for some material properties, but this may have been a consequence of the lack of older females in the subject pool. None of the compressive material properties were significantly correlated with age, but were more correlated with sample density. This finding differed for the tensile material properties, which showed stronger correlations with age. When comparing between tension and compression, significant differences were observed for all material properties except for the total SED, once the effects of loading rate and age had been accounted for. This was the first study to quantify the material properties of human rib cortical bone in compression. The results of this study demonstrated that rib and thorax finite element models should consider the effects of loading rate, loading mode, and age when incorporating material properties published in the literature.